Human-environmental interactions and seismic activity in a Late Bronze to Early Iron Age settlement center in the southeastern Caucasus - Von Suchodoletz, Hans; Kirkitadze, Giorgi; Koff, Tiiu; Fischer, Markus L.; Poch, Rosa M.; Khosravichenar, Azra; Schneider, Birgit; Glaser, Bruno; Lindauer, Susanne; Hoth, Silvan; Skokan, Anna; Navrozashvili, Levan; et al. (Frontiers in Earth Science, 2022)
Long-term human-environmental interactions in naturally fragile drylands are a focus of geomorphological and geoarchaeological research. Furthermore, many dryland societies were also affected by seismic activity. The semi-arid Shiraki Plain in the tectonically active southeastern Caucasus is currently covered by steppe and largely devoid of settlements. However, numerous Late Bronze to Early Iron Age city-type settlements suggest early state formation between ca. 3.2-2.5 ka that abruptly ended after that time. A paleolake was postulated for the lowest plain, and nearby pollen records suggest forest clearcutting of the upper altitudes under a more humid climate during the Late Bronze/Early Iron Ages. Furthermore, also an impact of earthquakes on regional Early Iron Age settlements was suggested. However, regional paleoenvironmental changes and paleoseismicity were not systematically studied so far. We combined geomorphological, sedimentological, chronological and paleoecological data with hydrological modelling to reconstruct regional Holocene paleoenvironmental changes, to identify natural and human causes and to study possible seismic events during the Late Bronze/Early Iron Ages. Our results show a balanced to negative Early to Mid-Holocene water balance probably caused by forested upper slopes. Hence, no lake but a pellic Vertisol developed in the lowest plain. Following, Late Bronze/Early Iron Age forest clear-cutting caused lake formation and the deposition of lacustrine sediments derived from soil erosion. Subsequently, regional aridification caused slow lake desiccation. Remains of freshwater fishes indicate that the lake potentially offered valuable ecosystem services for regional prehistoric societies even during the desiccation period. Finally, colluvial coverage of the lake sediments during the last centuries could have been linked with hydrological extremes during the Little Ice Age. Our study demonstrates that the Holocene hydrological balance of the Shiraki Plain was and is situated near a major hydrological threshold, making the landscape very sensitive to small-scale human or natural influences with severe consequences for local societies. Furthermore, seismites in the studied sediments do not indicate an influence of earthquakes on the main and late phases of Late Bronze/Early Iron Age settlement. Altogether, our study underlines the high value of multi-disciplinary approaches to investigate human-environmental interactions and paleoseismicity in drylands on millennial to centennial time scales.